2020
DOI: 10.3389/fpsyg.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Identity, Well-Being, and Willingness to Sacrifice in Personal and Collective Favorite Places: The Mediating Role of Well-Being

Abstract: In line with research indicating positive associations between well-being and personal and collective people-place bonding, and that collectivistic compared to individualistic commitment may have stronger associations with pro-environmental behavior, we investigated relationships between identity, well-being, and willingness to sacrifice (type of pro-environmental behavior) in personal and collective favorite places. A total of 884 respondents, living in three Swedish municipalities, participated in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 88 publications
(156 reference statements)
0
15
0
Order By: Relevance
“…In organizational behavior research, well-being was proposed to discuss employees' opinions about and attitudes toward work. Well-being referred to an individual engaging in, being satisfying with, and enjoying the work [8,23]. Obrenovic et al [24] considered that well-being presented sustainability, proactivity, and strong motivation to work.…”
Section: Polychronicity Fit and Well-beingmentioning
confidence: 99%
“…In organizational behavior research, well-being was proposed to discuss employees' opinions about and attitudes toward work. Well-being referred to an individual engaging in, being satisfying with, and enjoying the work [8,23]. Obrenovic et al [24] considered that well-being presented sustainability, proactivity, and strong motivation to work.…”
Section: Polychronicity Fit and Well-beingmentioning
confidence: 99%
“…Our results also indicate that communities had strong bonds internally and with places and thought of places as if they were "their own". Elements related to the sense of place literature were articulated among our key informants, particularly place attachment [8,10,16,67], as they were active in maintaining places that provided a shared identity for their community. The aspect of restoring places can often be seen in the civic ecology literature [5]; for example, in a study of oyster gardeners in New York [68], the authors found that sense of place was a motivating factor, together with meanings and memories.…”
Section: Place-making Agency and Communitymentioning
confidence: 99%
“…Such a societal shift has been highlighted as a deep leverage point for sustainability transformations [3], as it could enhance the already globally occurring ubiquitous urban environmental protection activities, such as gardening, tree planting, the maintenance of parks, local food production and ecological conservation/restoration and even the creation of entirely new urban ecosystems [4][5][6]. The literature in psychology and sociology suggests that such pro-environmental behavior in turn could shape inner motivations for broad-based environmental action, such as fostering a stronger connection to nature and enhanced levels of place-based well-being [7][8][9][10]. The massive scale and pace of global urbanization may lead to an alienation process in which a significant proportion of the future human population will find itself separated from sensory interaction with natural environments, which may lead to a broad-based social-ecological amnesia [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations